2007
DOI: 10.4049/jimmunol.178.10.6533
|View full text |Cite
|
Sign up to set email alerts
|

Peripherin Is a Relevant Neuroendocrine Autoantigen Recognized by Islet-Infiltrating B Lymphocytes

Abstract: Most of our knowledge of the antigenic repertoire of autoreactive B lymphocytes in type 1 diabetes (T1D) comes from studies on the antigenic specificity of both circulating islet-reactive autoantibodies and peripheral B lymphocyte hybridomas generated from human blood or rodent spleen. In a recent study, we generated hybridoma cell lines of infiltrating B lymphocytes from different mouse strains developing insulitis, but with different degrees of susceptibility to T1D, to characterize the antigenic specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Boitard et al proposed peripherin to be an auto-antigen related to type 1 diabetes (T1D) in 1992, though previous studies had shown that islet-infiltrating T-cells are major effectors of β-cell damage in type 1 diabetes, and these T-cells progressively destroy islet β-cells over a long, protracted period of insulitis; they doubted whether peripherin was the target of the T-cell immune reaction. Recently, Puertas et al 25 characterised the antigenic specificity of peripherin during T1D progression and suggested that peripherin-specific B lymphocytes might be attracted to the islet during disease. Carrillo et al 26 further demonstrated that anti-peripherin B lymphocytes are positively selected in the course of T1D development in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Boitard et al proposed peripherin to be an auto-antigen related to type 1 diabetes (T1D) in 1992, though previous studies had shown that islet-infiltrating T-cells are major effectors of β-cell damage in type 1 diabetes, and these T-cells progressively destroy islet β-cells over a long, protracted period of insulitis; they doubted whether peripherin was the target of the T-cell immune reaction. Recently, Puertas et al 25 characterised the antigenic specificity of peripherin during T1D progression and suggested that peripherin-specific B lymphocytes might be attracted to the islet during disease. Carrillo et al 26 further demonstrated that anti-peripherin B lymphocytes are positively selected in the course of T1D development in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with octamers at a final concentration of 8.5 μg/ml in FACS buffer (PBS/5% FCS) for 15 min on ice. For inhibition studies, A g7 /PRPH 467-507 C octamers were preincubated overnight with mAb 228 E1 at 4°C before cell staining (10). For PRPH C B cell distribution studies and co-staining of additional cell surface markers of islet-resident B cells, FITC-labeled anti-B220 or CD19 as well as PE-Cy5-labeled anti-CD3, anti-CD11c and anti-F4/80 (dump channel) were used.…”
Section: Methodsmentioning
confidence: 99%
“…About half of the B cell hybrids generated in this study recognized the peripheral nervous tissue (9). It was subsequently suggested that all neuronal-reactive B cells recognized the C-terminal portion of peripherin (PRPH), a cytoskeleton class III intermediate filament protein expressed in neuroendocrine tissues (10). These findings confirmed previous observations of anti-PRPH antibodies (Abs) in NOD mice (11, 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One issue that is not discussed but is important to appreciate is that most intra-islet B cells, at least in NOD mice, do not recognize antigens targeted by islet-associated T cells or T1D-associated antibodies. Rather, most of these intra-islet B cells recognize antigens expressed exclusively by the peri-islet Schwann cell, such as peripherin (Carrillo et al, 2005;Puertas et al, 2007). Immune targeting of the pancreatic glia has been implicated in the genesis of T1D (Tsui et al, 2008), and it is therefore possible that these autoreactive B cells contribute to this process.…”
Section: Immune Dysregulation Functional and Numerical Defects Of Invmentioning
confidence: 96%